Manajemen Resiko sebagai Faktor Kunci dalam Peningkatan Kinerja Operasional dan SDM - Muhammad Akhsan Tenrisau; Ayunita Tirtahati; Zulfikar Nurjana (Masyarakat Ekonomi Syariah Bogor, 2025)
Enterprise risk management creates value for the company including improving performance management, improving decision making that is adjusted to risk. The aim of this study was to examine the role of risk management in enhancing operational performance and solving HR issues within a company, particularly in relation to potential risks. A qualitative research approach was implemented, utilizing literature reviews from past studies. Findings from several previous studies indicated that risk management exerts a beneficial impact on bolstering operational performance and addressing human resources risks within a company. Additionally, it was discovered that both operational performance and internal company elements, especially HR (human resources), are positively impacted by the application of effective and efficient risk management, reinforcing the idea that risk management is a crucial factor. Future research is encouraged to incorporate more internal company factors impacted by risk management, expanding the validity and scope within the realm of risk management.